Penggunaan Kalimat Efektif pada Tajuk Rencana Surat Kabar Harian Riau Pos Edisi Desember 2020 - Nia Aprilina ZS; Jamilin Tinambunan (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This study analyzes the use of effective sentences in the editorial of the December 2020 edition of the Riau Pos newspaper. Effective sentences have a very large role for an article. The problem in this study is how to use effective sentences in the editorials of the December 2020 edition of the Riau Pos daily newspaper in terms of parallels in form and in terms of economy? The theory that is used as a guide in this research is Mustakim (1994). The method that the writer uses in this research is the method of content analysis and the research approach that the writer uses is a qualitative research. All data on effective sentences contained in the editorial of the December 2020 edition of the Riau Pos daily newspaper, from the alignment of forms, amounted to 15 incorrect data and 33 incorrect data. So, it can be concluded that from the parallel form of 650 sentences, which is 99.5% or about 635 sentences, it is categorized as very good in writing effective sentences in terms of form alignment, while sentences that are less effective from form alignment are 1.5% or 15 sentences, while the use of effective sentences in the editorial of the Riau Pos daily newspaper December 2020 edition of the savings of 650 sentences, namely 96.7% or about 617 sentences, was categorized as very good in writing effective sentences from frugality, while sentences that were less effective from frugality were 3.4 % or 33 sentences